2006
DOI: 10.1159/000094078
|View full text |Cite
|
Sign up to set email alerts
|

Cochleovestibular Dysfunction in Ankylosing Spondylitis

Abstract: Ankylosing spondylitis (AS) is a rheumatic disease characterized by chronic inflammation. The aim of this study was to evaluate the functions of the cochlea and the vestibular system in patients with AS. The study group consisted of 32 patients with AS and 30 healthy volunteers as a control group. Otorhinolaryngologic examinations were performed in all patients together with pure-tone audiometry, speech tests, impedancemetry, transient evoked otoacoustic emission (TEOAE) and electronystagmography (ENG). A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…As expected, age of the patients had correlation with hearing levels. Hearing loss in AS patients was revealed by recent studies [4][5][6][7]. Sensorineural nature of hearing loss is well documented, so there were only few discussions about the type of hearing loss [12,13], but the exact cause of underlying pathology of SNHL is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, age of the patients had correlation with hearing levels. Hearing loss in AS patients was revealed by recent studies [4][5][6][7]. Sensorineural nature of hearing loss is well documented, so there were only few discussions about the type of hearing loss [12,13], but the exact cause of underlying pathology of SNHL is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that sensorineural hearing loss (SNHL) is also one of the manifestations of this disease [4][5][6], but the cause of SNHL is unknown. Otoacoustic emission (OAE) findings of AS patients were reported significantly different than those of controls, especially in high frequencies, and suggested that damage of outer hair cells in AS patients causes SNHL [7,8]. The aim of this study was to investigate the hearing status and cochlear functions of AS patients and find out any correlation between hearing status and disease activity.…”
Section: Introductionmentioning
confidence: 97%
“…Alatas et al [4] observed SNHL both at low and high frequencies in patients with AS. Erbek et al [8] found statistically significant difference at high frequencies in 32 patients with AS.…”
Section: Discussionmentioning
confidence: 96%
“…Alatas et al [4] , did not find any statistically significant difference in the ABR results between patients and the control group. Erbek et al [8] found that the rates of reproducibility in transient evoked otoacoustic emission testing (TEOAE) were significantly lower in patients with AS than those in controls. Daglı et al [7] determined the same result with distortion product otoacoustic emission testing (DPOAE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation